Canine anal sac gland carcinoma with regional lymph node metastases treated with sacculectomy and lymphadenectomy: Outcome and possible prognostic factors. (12th October 2021) - Tanis, Jean‐Benoit; Simlett‐Moss, Angharad B.; Ossowksa, Malgorzata; Maddox, Thomas W.; Guillem, James; Lopez‐Jimenez, Cristobal; Polton, Gerry; Burrow, Rachel; Finotello, Riccardo
Abstract: The staging system commonly used in canine anal sac gland carcinoma (ASGC) is a revised Tumour‐Node‐Metastasis (TNM) system published in 2007. This staging system consists in four stages and, for dogs with nodal metastases, the size of the metastatic lymph node (mLN) defines the N stage. However, we hypothesise that (1) the mLN size has no prognostic significance when the mLN can be excised, (2) a high number of mLNs is associated with poorer prognosis and (3) the measurement of the mLN on imaging is not reproducible. To investigate these hypotheses, medical records and diagnostic images of dogs with ASGC and mLN, treated with sacculectomy and lymphadenectomy, with or without chemotherapy, were reviewed. Interobserver variability for mLN measurement was assessed. Prognostic factors including mLN size and number were investigated. Time to documented progression (TDP) and disease‐specific survival (DSS) were evaluated. Progression‐free interval (PFI) was analysed with interval‐censored data analysis. Fifty‐seven dogs were included. The median PFI, TDP and DSS were 110 (95%CI 61.5–185.5), 196 (95%CI 162–283) and 340 days (95%CI 321–471), respectively. For measurement of the largest mLN, interobserver agreement was excellent but limits of agreement reached 39.7%. Neither the size of the largest mLN nor the use of adjuvant chemotherapy were associated with outcome. The number of mLNs was associated with outcome and having more than four mLNs was associated with shorter PFI ( p  < .001), TDP ( p  = .004) and DSS ( p  < .001). While mLN size measurement was not consistently reproducible and did not influence outcome in our cohort, number of mLNs did. Further studies are required for development of a revised staging system.